IN VITRO ANTI-NEUROINFLAMMATORY EFFECT OF GENISTEIN (4',5,7-TRIHYDROXYISOFLAVONE) ON MICROGLIA HMC3 CELL LINE, AND IN SILICO EVALUATION OF ITS INTERACTION WITH ESTROGEN RECEPTOR-β - MA’ARIF, BURHAN; MUSLIKH, FAISAL A.; ANGGRAINI, WIRDA; TAEK, MAXIMUS M.; LASWATI, HENING; AGIL, MANGESTUTI (International Journal of Applied Pharmaceutics, 2021)
Objective: This study was aimed to evaluate the role of genistein or 4',5,7-trihydroxyisoflavone as a phytoestrogen in the treatment of estrogen deficiency-induced neuroinflammatory. The specific objectives of this study were to determine the anti-neuroinflammatory effect of genistein through measurement of MHC II and Arg1 expressions on microglia HMC3 cell line, as well as to prove that the effect occurs in an ER-dependent manner, through the measurement of free-ERβ expression. Methods: The cells were cultured in 24-well microplates, induced with 10 ng IFN-γ, and incubated for 24 h to activate the cell to M1 phenotype which has pro-inflammatory characteristics. Genistein with a concentration of 50 μM was added to the cells. The expression of MHC II, Arg1, and free-ERβ as markers was tested through an immunocytochemistry method and measured using the CLSM instrument. In silico approach was also conducted to determine the interaction between genistein and ERβ, compared to 17β-estradiol. Genistein structure was prepared with Avogadro 1.0.1, and molecular docking was done using PyRx 0.8 software. Biovia Discovery Studio Visualizer 2016 was used to visualize the structure of genistein against 3OLS protein. The physicochemical characteristics of genistein were analyzed using the SwissADME web tool. Results: Genistein can decrease MHC II expression and increase Arg1 expression in microglia HMC3 cells compared to negative controls (p<0.005), with expression value of 472.577±26.701 AU and 114.299±6.578 AU. But, genistein cannot decrease the free-ERβ expression in cells (p<0.005). The results of in silico analysis showed that genistein is an ERβ agonist. Conclusion: Genistein shows anti-neuroinflammatory effects by decreasing the MHC II expression and increasing Arg1 expression in the microglia HMC3 cell line. However, this effect does not occur through the binding of genistein to ERβ, but it is likely to occur through the binding of genistein with other types of ER.